'We're effectively becoming immigration officers': social care managers' experiences of the risk work of employing migrant care workers. (19th May 2018) - Manthorpe, Jill; Harris, Jess; Stevens, Martin; Moriarty, Jo
Abstract : In the UK care sector, as much as other fields of work, managers need to check and monitor the immigration status of their staff. In this article, we examine accounts from care home and home care managers of making decisions about recruitment and employment practices placing these in the context of risk work. We use data from a secondary analysis of interviews with 121 social care managers that took place in four contrasting English local authority areas in two rounds over the period 2009–2014. In the interviews, we explored managers' views and experiences of employing or deciding not to recruit migrant workers and the extra work this potentially entailed. We identified three major themes in these interviews: vigilance, being caught, and shifting resources. The Vigilance in recruitment and managing staff theme highlighted managers' experiences of and concerns about implementing the regulations around employment permissions and indicated their feelings that it was essential to comply with new government regulations relating to migrant workers. The Being caught theme was based on managers' fears about the risks of being in breach of the regulations and worry about the severity of the penalties. The Shifting sources theme highlighted managers' continued work in reaching out to fresh sources of recruitment as a response to changes in immigration regulations. Our findings expose the potentially stressful nature of managers' roles in implementing new regulations and managing the risks of non-compliance. This new aspect of risk work reveals the tensions of managers' role in performing their obligations to scrutinise documentation and abide by changing regulations while still running their services. As the UK moves to Brexit (leaving the European Union), these tensions look set to increase in the context of further migrant working regulations and amendments to immigration permissions.